Effects of Different Lateral Stiffeners to The Seismic Performance of 21-Storey Apartment Building Structure in Yogyakarta - Kuncoro, Ardityo Dwi; Widodo, Slamet (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Rapid high-rise construction, especially in seismically active Java and Yogyakarta, demands lateral stiffness consistent with SDG 9 and SNI 1726:2019 to ensure resilience against earthquake actions. Shear walls and steel bracing are widely used to control interstory drift and stability, yet comparative evidence tailored to Yogyakarta remains limited. Methods used by using a finite-element model of a 21-story apartment and perform elastic response-spectrum analyses based on SNI 1726:2019. Four lateral systems are compared, emphasizing concentric X-bracing (CBF-X) and eccentric K-bracing (EBF-K). Performance metrics include interstory drift, P-Δ stability coefficients, and horizontal and vertical irregularities. Models incorporate rigid diaphragm assumptions, gravity and lateral load combinations, and cracked-section modifiers for shear walls consistent with code recommendations. Member forces were also checked. The results indicate that all structural configurations satisfy the standard requirements of SNI 1726-2019. The smallest interstory drift occurs in the structure with the K-bracing system, with minimum values in the X direction ranging from 3.992 mm and maximum 19.395 mm, and in the Y direction minimum from 1.172 mm and maximum 36.344 mm. The P–Delta effect shows the smallest stability coefficients in the K-bracing system, with X-direction minimum values of 0.0019 mm and maximum 0.0256 mm, and Y-direction minimum values of 0.0018 mm and maximum 0.0104 mm. Analysis of structural irregularities using X-ray diffraction yields superior results compared to other structures. For a tall building in Yogyakarta’s seismic setting, combining shear walls with steel bracing is effective and code-compliant. Among the examined schemes, EBF-K minimizes drift and P-Δ effects, offering superior lateral stiffness and energy dissipation, whereas CBF-X excels in meeting irregularity criteria and maintaining global stability. The results provide location-specific guidance for selecting lateral systems in Indonesian high-rise design and support performance-oriented detailing under SNI 1726:2019